Evolution of crop models: Modeling approaches and software development - Aditya Kapoor; Sahila Beegum; David Fleisher; Dennis Timlin; Chittaranjan Ray; Vangimalla Reddy (Ecological Modelling, 2026)

A national health impact assessment of achieving tree canopy goals in US urban areas - Michelle C. Kondo; Tamara Iungman; Evelise Pereira Barboza; Dexter H. Locke; Ray Yeager; Dustin Fry; Ava-Clare Steed; Marcia Pescador Jiménez; David Rojas-Rueda; Mark Nieuwenhuijsen (Environmental Research, 2026)

The SPAR facility: insights on a legacy with continued relevance for agriculture - Muhammad Adeel Hassan; Sahila Beegum; Christine Yao-Yun Chang; Dennis Timlin; David Fleisher; Chittaranjan Ray; Vangimalla Reddy; Kambham Raja Reddy (Computers and Electronics in Agriculture, 2026)

Transformation of inorganic reactive nitrogen species in a simulated vadose zone - Yvon Ukwishaka; Daniel N. Miller; Preetismita Borah; Daniel D. Snow; Michael Kaiser; Chittaranjan Ray; David Fleisher; Dennis Timlin; Vangimalla Reddy; Arindam Malakar (Science of The Total Environment, 2026)

Systematic evaluation of Tox21 compounds that target β-adrenergic receptors and their role in cardiotoxicity - Xi Luo; Li Zhang; Srilatha Sakamuru; Precious A. Adesina; Jinghua Zhao; Menghang Xia; Tuan Xu; Deborah K. Ngan; Jameson Travers; Savannah Wood; Ray Sukhawanit; Anthony Garrison; et al. (Toxicology and Applied Pharmacology, 2025)

Monsoon-driven oceanographic variability and habitat conditions of moonfish in southwestern Taiwan: ecological insights for sustainable fisheries - Aratrika Ray; Sandipan Mondal; David Mendes; Kennedy Edeye Osuka; Arpita Ghosh; Ming-An Lee; Quang-Huy Lu; Jun-Hong Wu; Yi-Chen Wang; Jia-Sin He (Reviews in Fish Biology and Fisheries, 2025)

Periodic cropping of pasture for summer-grazed turnips leads to substantial carbon loss - Aaron M. Wall; Jordan P. Goodrich; Seager Ray; David I. Campbell; Louis A. Schipper (Agricultural and Forest Meteorology, 2025)

Manistee, a new Round-White Early to Mid-Season Maturing Potato Variety with Excellent Long-Term Storage Potential - David S. Douches; Joseph J. Coombs; William L. Behling; Ray Hammerschmidt; Greg E. Steere; Matthew L. Zuehlke; Christopher M. Long (American Journal of Potato Research, 2025)
Manistee is a round white chip-processing potato ( Solanum tuberosum ) variety developed for long-term storage. Evaluated as MSL292-A, Manistee is a selection from a cross between Snowden and the chip-processing breeding line MSH098-2. The tubers of Manistee are compressed, round with shallow eyes and early to mid-season maturity. Field testing and on-farm trials show that this variety has high yield potential with specific gravity comparable to Snowden and similar to better tolerance to blackspot bruise. Manistee was formally released in 2013 and has demonstrated reliable and excellent long-term storage chip-processing quality up to eight months post-harvest which extends the chip-processing storage season beyond Snowden. Furthermore, preliminary studies with Manistee, Snowden, Lamoka and Pike tuber disks demonstrated that Manistee started the wound healing process faster than Lamoka and Pike and slightly faster than Snowden which supports observations of stable and reliable commercial storage of the tubers for chip-processing.

Examining the impacts of spatial closures in the Gulf Menhaden fishery - Robert T. Leaf; Wei Wu; Ray M. Mroch; Robert Trigg; David Duval (Frontiers in Marine Science, 2025)
Policymakers in the northern Gulf of America have proposed various spatial closures in recent years as a management tool for the Gulf Menhaden Brevoortia patronus fishery. In this work, we aim to understand how the seasonal movement of the stock will impact the efficacy of spatial restrictions by examining the short-term impacts of simulated area closures of 1.6, 3.2, and 4.8 km adjacent to land on the commercial Gulf Menhaden fishery using commercial logbook data from 2006 to 2009 and 2011. We used bootstrap resampling (n = 1,000) of trip-level data to describe five descriptive metrics. These were the mean set-specific catch per unit effort (CPUE, metric tons, mt set -1 ), the mean number of sets deployed on each trip, the mean trip-specific CPUE (mt minute -1 ), the median distance (km) traveled to the first set, and the median distance (km) traveled among subsequent sets (for trips with at least two sets). We explored the impacts of closures by comparing the month-specific distributions of the descriptive metrics from all trips to those calculated using only those trips with all sets outside of a particular restricted area. Using the simulation, we evaluated the resulting spatial differences in fishing effort that would occur. The results of the simulation indicated that, in all restriction scenarios for all months, the spatial restrictions served to increase the travel distance to the first set and to reduce the mean number of sets taken. Set-specific and trip-specific CPUE are reduced in the restriction scenarios. We found that the reduction of total harvest (mt) for the 1.6 km restriction regime was 4.3 to 7.2%, 9.1 to 12.0% in the 3.2 km restriction regime, and 12.7 to 15.4% in the 4.8 km restriction regime. This work provides information about the impacts on the fishery that result from area closures. Such information is necessary to evaluate the efficacy and impacts of spatial closures for the Gulf Menhaden fishery.

Computational NMR enhances metabolomic analysis and sustainability - Matthias Niemitz; Petrus Korhonen; Juuso Lehtivarjo; G. Joseph Ray; David C. Lankin; Charlotte A. Corbett; Shao-Nong Chen; Guido F. Pauli (Phytochemistry Letters, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Real-Time detection of sewer water levels and blockages using UHF-RFID sensors - Sundra R. Tatiparthi; Yashika G. De Costa; David Wyllie; Ray Y. Zhong; Shihu Hu; Zhiguo Yuan; Colin N. Whittaker; Wei-Qin Zhuang (Water Research, 2025)

Efficacy of unbaited and baited green multi-funnel traps for detection of Agrilus species and other wood-boring beetle taxa - Giacomo Santoiemma; Jon Sweeney; Everett G. Booth; Giacomo Cavaletto; Gianfranco Curletti; Sarah M. Devine; Joseph A. Francese; Emily K. L. Franzen; Filippo Giannone; Mischa Giasson; Jerzy M. Gutowski; Cory Hughes; et al. (Journal of Pest Science, 2025)
Semiochemical-baited traps are a key component of post-border surveillance for detection of non-native and potentially invasive bark and wood-boring beetles (Buprestidae, Cerambycidae, Curculionidae: Scolytinae) at risk of introduction in untreated woody materials used in global trade. Because the particular species that may arrive with imported goods is unknown, plant protection agencies need trapping protocols that effectively survey all three taxa. Baiting traps with host volatiles and aggregation/sex pheromones of longhorn beetles increases efficacy of detecting Cerambycidae and Scolytinae, but its effect on detection of Agrilus species and other jewel beetles is unknown. In this multi-country trapping study we found that the addition of ethanol and common aggregation/sex pheromones of longhorn beetles to green multi-funnel traps placed in the mid-upper forest canopy had negative effects on abundance of Agrilus species and other jewel beetles collected but no effect on their species richness, and significant positive effects on species richness and abundance of Cerambycidae and Scolytinae. Baiting green canopy traps with longhorn beetle pheromones increased the efficacy of traps for detecting total target taxa of bark and wood-boring beetles at risk of international movement in untreated woody materials. This information is beneficial for the design of multi-taxa surveys, potentially saving money and resources without decreasing trapping efficacy.

Improvements in the Seasonal Prediction of the Mid‐Summer Drought Based on the North American Multimodel Ensemble - David Maximiliano Zermeño‐Díaz; Pallav Ray (International Journal of Climatology, 2025)
Skillful prediction of the Mid‐Summer Drought (MSD) is important for various socioeconomic sectors in southern Mexico, Central America and the Caribbean. However, operational forecasting errors of the MSD have rarely been evaluated systematically. In this study, we address this research gap by examining operational forecasts of the MSD derived from the North American Multimodel Ensemble (NMME; 1991–2020). We assess these forecasts before and after applying a Model Output Statistics (MOS) scheme based on Canonical Correlation Analysis (CCA). Before applying MOS, only a couple of forecasts exhibited a bimodal signal between July and September, but none of them reproduced the particular signals of the MSD; they generally suffered from two main errors: excessively weak precipitation during the June–September season (particularly in June) and a weak peak in July instead of a relative minimum. While the root cause of these errors can be associated with warm sea surface temperature (SST) bias in the tropical eastern Pacific and cold SST bias in the Gulf of Mexico, Caribbean Sea and northwestern tropical Atlantic, their immediate cause is an erroneous evolution of the eastern Pacific Intertropical Convergence Zone (ITCZ). During June and September, the eastern Pacific ITCZ remains too far south near the equator, while in July and August it expands and intensifies but stays too close to the coasts of southern Mexico and Central America, failing to migrate westward. After applying MOS, the forecasts showed high skill scores during the onset of the MSD (July and August) but not in the months before and after (June and September). As revealed by the CCA analysis, this improved skill is due to the MOS‐corrected forecasts' improved representation of a key relationship: drier MSD episodes are associated with a stronger westward SST gradient between the eastern tropical Pacific Ocean and the Caribbean Sea. Models that adequately capture this relationship exhibit reduced uncertainty in forecasting MSD intensity. This finding can provide a valuable pathway to mitigate uncertainties in projecting future changes in MSD intensity under different climate change scenarios.

Coupling ecological concepts with an ocean-colour model: Parameterisation and forward modelling - Xuerong Sun; Robert J.W. Brewin; Shubha Sathyendranath; Giorgio Dall’Olmo; David Antoine; Ray Barlow; Astrid Bracher; Malika Kheireddine; Mengyu Li; Dionysios E. Raitsos; Fang Shen; Gavin H. Tilstone; et al. (Remote Sensing of Environment, 2025)

Genomic affinity following restoration of a locally extirpated species: a case study of desert bighorn sheep in Texas - Emily A. Wright; Joseph D. Manthey; Michael R. Buchalski; Bonnie R. McKinney; David A. Ray; Caleb D. Phillips; Robert D. Bradley (Conservation Genetics, 2024)

2.5D Hexahedral Meshing for Reservoir Simulations - David Lopez; Yoann Coudert-Osmont; David Desobry; Alexandre Benedicto; Wan-Chiu Li; Cédric Borgese; Nicolas Ray; Dmitry Sokolov; Jeanne Pellerin (Mathematical Geosciences, 2024)

Simulating climate change effects on soil carbon dynamics in a soybean–maize ecosystem: Using improved CO2 emission and transport models - Wenguang Sun; David Fleisher; Dennis Timlin; Chittaranjan Ray; Zhuangji Wang; Sahila Beegum; Vangimalla Reddy (European Journal of Agronomy, 2024)

Efficacy of trapping protocols for Agrilus jewel beetles: a multi-country assessment - Giacomo Santoiemma; David Williams; Everett G. Booth; Giacomo Cavaletto; James Connell; Gianfranco Curletti; Maarten de Groot; Sarah M. Devine; Abigail Enston; Joseph A. Francese; Emily K. L. Franzen; Mischa Giasson; et al. (Journal of Pest Science, 2024)
The genus Agrilus is one of the most diverse insect genera worldwide. The larval feeding activity causes extensive damage in both forests and orchards. In addition, more than 30 species have been introduced outside their native range so far, including the emerald ash borer Agrilus planipennis Fairmaire. Thus, the availability of efficient trapping protocols for early detection of Agrilus species at entry points is of utmost importance. In this study we tested whether trapping protocols developed for surveillance of A. planipennis in North America were also effective for other Agrilus species. In particular, through a multi-country assessment we compared the efficacy of detecting Agrilus species on: (i) green glue-coated prism traps vs. green Fluon-coated multi-funnel traps when baited with the green leaf volatile ( Z )-3-hexenol or left unbaited; and (ii) green multi-panel traps vs. green multi-panel traps baited with dead adult Agrilus beetles (decoys). A total of 23,481 individuals from 45 Agrilus species were caught. Trap design significantly affected both species richness and abundance of Agrilus species in several of the countries where the trapping experiments were carried out, and green prism traps outperformed green multi-funnel traps in most cases. On the contrary, the addition of a ( Z )-3-hexenol lure or dead adult beetle decoys on to traps did not improve trap catches. Our study highlights that reliable trap models to survey Agrilus species are already available, but also that there is the clear need to further investigate chemical ecology of Agrilus species to develop semiochemical lures that can improve detection efficacy.

Quantifying minimum site occupancy requirements of common forest tree species in northern New England, USA: Implications for stocking assessment - David Ray; Robert Seymour; Shawn Fraver; John-Pascal Berrill; Laura Kenefic; Nicole Rogers; Aaron Weiskittel (Forest Ecology and Management, 2024)

Evaluating the Development and Application of Stand Density Index for the Management of Complex and Adaptive Forests - Emmerson Chivhenge; David G. Ray; Aaron R. Weiskittel; Christopher W. Woodall; Anthony W. D’Amato (Current Forestry Reports, 2024)

Factors influencing the carbon footprint of milk production on dairy farms with different feeding strategies in western Europe - Marion Sorley; Imelda Casey; David Styles; Pilar Merino; Henrique Trindade; Martin Mulholland; Cesar Resch Zafra; Ray Keatinge; André Le Gall; Donal O'Brien; James Humphreys (Journal of Cleaner Production, 2024)

HydroShare retrospective: Science and technology advances of a comprehensive data and model publication environment for the water science domain - David G. Tarboton; Daniel P. Ames; Jeffery S. Horsburgh; Jonathan L. Goodall; Alva Couch; Richard Hooper; Jerad Bales; Shaowen Wang; Anthony Castronova; Martin Seul; Ray Idaszak; Zhiyu Li; et al. (Environmental Modelling & Software, 2024)

Identifying critical microbes in guayule-microbe and microbe-microbe associations - Yongjian Chen; David A. Dierig; Guangyao Wang; Diaa Eldin M. Elshikha; Dennis T. Ray; Albert Barberán; Raina M. Maier; Julia W. Neilson (Plant and Soil, 2024)

Does drought stress eliminate the benefit of elevated CO2 on soybean yield? Using an improved model to link crop and soil water relations - Wenguang Sun; David Fleisher; Dennis Timlin; Chittaranjan Ray; Zhuangji Wang; Beegum Sahila; Vangimalla Reddy (Agricultural and Forest Meteorology, 2023)

Relative Density as a Standardizing Metric for the Development of Size-Density Management Charts - David Ray; Robert Seymour; Shawn Fraver; John-Pascal Berrill; Laura Kenefic; Nicole Rogers; Aaron Weiskittel (Journal of Forestry, 2023)
Stand density management is central to achieving diverse silvicultural objectives. Decision-support tools in this domain range from expert opinion to sophisticated computer models that vary by forest type, region, and organization. The graphical frameworks represented by density management diagrams (DMDs) and stocking guides (SGs), collectively called size-density management charts (SDMCs), are well established and balance quantitative rigor with user accessibility. Regional differences in species composition and site quality are known to influence maximum size-density relationships, historically limiting the development of reliable charts. Advances in statistical modeling and data availability are overcoming this issue and should encourage more widespread use. We briefly review the history of SDMCs and propose the adoption of relative density based on stand density index as a logical metric for linking the DMD and SG formats. Examples of SDMC construction and use are illustrated for spruce-fir stands in Maine, USA. Study Implications: Recognition of the importance of stand density management has increased in recent years owing to its potential to address threats such as susceptibility to catastrophic wildfires and forest health issues exacerbated by environmental stress. Natural resource managers will benefit from adopting a language around density management that is both biologically grounded and consistent. A relative density framework is compatible with the two primary types of size-density management charts and thus meets this objective well. Relative density provides an ideal launching point for articulating levels of stand density, or stocking, to meet diverse management objectives determined under relevant socioecological constraints.

Benefits, concerns, and solutions of fishing for tunas with drifting fish aggregation devices - Maite Pons; David Kaplan; Gala Moreno; Lauriane Escalle; Francisco Abascal; Martin Hall; Victor Restrepo; Ray Hilborn (Fish and Fisheries, 2023)
Drifting fish aggregating devices (dFADs) are human‐made floating objects widely used by tropical tuna purse seine (PS) fisheries to increase catch of target species. However, dFAD use has several negative impacts, including increased potential for overfishing, higher juvenile tuna catch, higher bycatch compared to other PS fishing modes, ghost‐fishing, and generation of marine litter. Based on these impacts, some stakeholders, especially environmental non‐governmental organizations and other competing fishing industries, suggest that dFADs should be completely banned. We list the pros and cons of dFAD fishing; address how to improve current management; and suggest solutions for the sustainability of dFAD fishing in the long term. A dFAD ban would lead to major changes in the availability and sourcing of tuna for human consumption and decrease the licensing revenue received by many developing states. Most importantly, we argue that tools exist today to manage for, reduce or eliminate most of the negative impacts of dFADs (e.g., bans on discards, limits on active dFADs, biodegradable non‐entangling constructions, time‐area deployment closures, recovery programs, and full data transparency, among others). Management decisions based on sound scientific reasoning are needed to address the legitimate concerns surrounding dFAD use and ensure the sustainability of both pelagic and coastal ecosystems and tropical tuna PS fisheries.

The Ontology of Biological Attributes (OBA)—computational traits for the life sciences - Ray Stefancsik; James P. Balhoff; Meghan A. Balk; Robyn L. Ball; Susan M. Bello; Anita R. Caron; Elissa J. Chesler; Vinicius de Souza; Sarah Gehrke; Melissa Haendel; Laura W. Harris; Nomi L. Harris; et al. (Mammalian Genome, 2023)
Existing phenotype ontologies were originally developed to represent phenotypes that manifest as a character state in relation to a wild-type or other reference. However, these do not include the phenotypic trait or attribute categories required for the annotation of genome-wide association studies (GWAS), Quantitative Trait Loci (QTL) mappings or any population-focussed measurable trait data. The integration of trait and biological attribute information with an ever increasing body of chemical, environmental and biological data greatly facilitates computational analyses and it is also highly relevant to biomedical and clinical applications. The Ontology of Biological Attributes (OBA) is a formalised, species-independent collection of interoperable phenotypic trait categories that is intended to fulfil a data integration role. OBA is a standardised representational framework for observable attributes that are characteristics of biological entities, organisms, or parts of organisms. OBA has a modular design which provides several benefits for users and data integrators, including an automated and meaningful classification of trait terms computed on the basis of logical inferences drawn from domain-specific ontologies for cells, anatomical and other relevant entities. The logical axioms in OBA also provide a previously missing bridge that can computationally link Mendelian phenotypes with GWAS and quantitative traits. The term components in OBA provide semantic links and enable knowledge and data integration across specialised research community boundaries, thereby breaking silos.

Spatial and temporal variability in summertime dissolved carbon dioxide and methane in temperate ponds and shallow lakes - Nicholas E. Ray; Meredith A. Holgerson; Mikkel Rene Andersen; Jānis Bikše; Lauren E. Bortolotti; Martyn Futter; Ilga Kokorīte; Alan Law; Cory McDonald; Jorrit P. Mesman; Mike Peacock; David C. Richardson; et al. (Limnology and Oceanography, 2023)
Small waterbodies have potentially high greenhouse gas emissions relative to their small footprint on the landscape, although there is high uncertainty in model estimates. Scaling their carbon dioxide (CO 2 ) and methane (CH 4 ) exchange with the atmosphere remains challenging due to an incomplete understanding and characterization of spatial and temporal variability in CO 2 and CH 4 . Here, we measured partial pressures of CO 2 ( p CO 2 ) and CH 4 ( p CH 4 ) across 30 ponds and shallow lakes during summer in temperate regions of Europe and North America. We sampled each waterbody in three locations at three times during the growing season, and tested which physical, chemical, and biological characteristics related to the means and variability of p CO 2 and p CH 4 in space and time. Summer means of p CO 2 and p CH 4 were inversely related to waterbody size and positively related to floating vegetative cover; p CO 2 was also positively related to dissolved phosphorus. Temporal variability in partial pressure in both gases weas greater than spatial variability. Although sampling on a single date was likely to misestimate mean seasonal p CO 2 by up to 26%, mean seasonal p CH 4 could be misestimated by up to 64.5%. Shallower systems displayed the most temporal variability in p CH 4 and waterbodies with more vegetation cover had lower temporal variability. Inland waters remain one of the most uncertain components of the global carbon budget; understanding spatial and temporal variability will ultimately help us to constrain our estimates and inform research priorities.

Projected long-term climate trends reveal the critical role of vapor pressure deficit for soybean yields in the US Midwest - Wenguang Sun; David Fleisher; Dennis Timlin; Chittaranjan Ray; Zhuangji Wang; Sahila Beegum; Vangimalla Reddy (Science of The Total Environment, 2023)

Critical Market Tipping Points for High-Grade White Oak Inventory Decline in the Central Hardwood Region of the United States - Gaurav Dhungel; David Rossi; Jesse D Henderson; Robert C Abt; Ray Sheffield; Justin Baker (Journal of Forestry, 2023)
This study expands the spatial scope of the Subregional Timber Supply (SRTS) model to include states in the central hardwood region and examine critical market tipping points of high-grade (large diameter) white oak under a set of illustrative scheduled demand scenarios. In light of the growing concern for future white oak timber supply, we illustrate the sensitivity of future inventory tipping points to market structure and price responsiveness. Particularly, we examined the importance of market demand parameters, including growth rates for product demand and supply/demand elasticities, in influencing future inventory trajectories in different subregions over the projection horizon. Results of this study indicate that more elastic demand and more inelastic supply response concomitantly defers the time before inventory culminates. This modeling framework shows promise in examining key ecological, climatic, and economic interrelationships that will drive future resource changes.

A pilot study investigating feasibility of mainstreaming germline BRCA1 and BRCA2 testing in high-risk patients with breast and/or ovarian cancer in three tertiary Cancer Centres in Ireland - Terri Patricia McVeigh; Karl J. Sweeney; Donal J. Brennan; Una M. McVeigh; Simon Ward; Ann Strydom; Sheila Seal; Katherine Astbury; Paul Donnellan; Joanne Higgins; Maccon Keane; Michael J. Kerin; et al. (Familial Cancer, 2023)

Seasonal differences in day-roost selection by Northern long-eared bats (Myotis septentrionalis) in Louisiana and a meta-analytical comparison across North America - Carlos J. Garcia; David A. Ray; Roger W. Perry; Richard D. Stevens (Forest Ecology and Management, 2023)

Short‐term plant–soil feedback experiment fails to predict outcome of competition observed in long‐term field experiment - Noelle G. Beckman; Ray Dybzinski; David Tilman (Ecology, 2023)
Mounting evidence suggests that plant–soil feedbacks (PSF) may determine plant community structure. However, we still have a poor understanding of how predictions from short‐term PSF experiments compare with outcomes of long‐term field experiments involving competing plants. We conducted a reciprocal greenhouse experiment to examine how the growth of prairie grass species depended on the soil communities cultured by conspecific or heterospecific plant species in the field. The source soil came from monocultures in a long‐term competition experiment (LTCE; Cedar Creek Ecosystem Science Reserve, MN, USA). Within the LTCE, six species of perennial prairie grasses were grown in monocultures or in eight pairwise competition plots for 12 years under conditions of low or high soil nitrogen availability. In six cases, one species clearly excluded the other; in two cases, the pair appeared to coexist. In year 15, we gathered soil from all 12 soil types (monocultures of six species by two nitrogen levels) and grew seedlings of all six species in each soil type for 7 weeks. Using biomass estimates from this greenhouse experiment, we predicted coexistence or competitive exclusion using pairwise PSFs, as derived by Bever and colleagues, and compared model predictions to observed outcomes within the LTCE. Pairwise PSFs among the species pairs ranged from negative, which is predicted to promote coexistence, to positive, which is predicted to promote competitive exclusion. However, these short‐term PSF predictions bore no systematic resemblance to the actual outcomes of competition observed in the LTCE. Other forces may have more strongly influenced the competitive interactions or critical assumptions that underlie the PSF predictions may not have been met. Importantly, the pairwise PSF score derived by Bever et al. is only valid when the two species exhibit an internal equilibrium, corresponding to the Lotka–Volterra competition outcomes of stable coexistence and founder control. Predicting the other two scenarios, competitive exclusion by either species irrespective of initial conditions, requires measuring biomass in uncultured soil, which is methodologically challenging. Subject to several caveats that we discuss, our results call into question whether long‐term competitive outcomes in the field can be predicted from the results of short‐term PSF experiments.

Getting the most out of maths: How to coordinate mathematical modelling research to support a pandemic, lessons learnt from three initiatives that were part of the COVID-19 response in the UK - Ciara E. Dangerfield; I. David Abrahams; Chris Budd; Matt Butchers; Michael E. Cates; Alan R. Champneys; Christine S.M. Currie; Jessica Enright; Julia R. Gog; Alain Goriely; T. Déirdre Hollingsworth; Rebecca B. Hoyle; et al. (Journal of Theoretical Biology, 2023)

Quantitative Analysis of Stress-Induced Hyperglycemia and Intracranial Blood Volumes for Predicting Mortality After Intracerebral Hemorrhage - Claire Delpirou Nouh; Bappaditya Ray; Chao Xu; Bin Zheng; Gopichand Danala; Ahmed Koriesh; Kimberly Hollabaugh; David Gordon; Evgeny V. Sidorov (Translational Stroke Research, 2022)

Rebound effect and sustainability science: A review - David Font Vivanco; Jaume Freire‐González; Ray Galvin; Tilman Santarius; Hans Jakob Walnum; Tamar Makov; Serenella Sala (Journal of Industrial Ecology, 2022)
Rebound effects have been historically studied through narrow framings which may overlook the complexity of sustainability challenges, sometimes leading to badly informed conclusions and policy recommendations. Here we present a critical literature review of rebound effects in the context of sustainability science in order to (1) map existing rebound research which goes beyond mainstream approaches, (2) unveil and classify current knowledge gaps in relation to sustainability science, (3) outline a research agenda, and (4) provide a knowledge base to support the design of effective policies toward sustainable development. We analyzed the literature in accordance with seven criteria for sustainable assessment: boundary orientedness, comprehensiveness, integratedness, stakeholder involvement, scalability, strategicness, and transparency. Our review identified three main issues: (1) the failure to address the multidimensionality of rebound effects, whereby both negative and positive outcomes may arise simultaneously, (2) the shift toward absolute rebound metrics which enables the contextualization of its effect with respect to science and policy goals, and (3) a general lack of attention to behavioral effects. We conclude that addressing these issues will help rebound research gain explanatory power and relevance for key decision‐makers. We envision that with better alignment with sustainability science, future rebound research could help elucidate trade‐offs in policies, including why certain strategies such as those based on the circular economy might fall short of expectations, and why achieving key goals and targets such as the sustainable development goals is so challenging. This knowledge is crucial for promoting a prioritization of actions and a concrete transition toward sustainability.

Understanding the role of topography on the diurnal cycle of precipitation in the Maritime Continent during MJO propagation - Haochen Tan; Pallav Ray; Bradford Barrett; Jimy Dudhia; Mitchell Moncrieff; Lei Zhang; David Zermeno-Diaz (Climate Dynamics, 2022)

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

Chronoimmunology: from preclinical assessments to clinical applications - Henrik Oster; David W. Ray (Seminars in Immunopathology, 2022)

Glucocorticoid circadian rhythms in immune function - Iwona Olejniczak; Henrik Oster; David W. Ray (Seminars in Immunopathology, 2022)

Area‐based management of blue water fisheries: Current knowledge and research needs - Ray Hilborn; Vera N. Agostini; Milani Chaloupka; Serge M. Garcia; Leah R. Gerber; Eric Gilman; Quentin Hanich; Amber Himes‐Cornell; Alistair J. Hobday; David Itano; Michel J. Kaiser; Hilario Murua; et al. (Fish and Fisheries, 2022)
The pelagic fisheries beyond the continental shelves are currently managed with a range of tools largely based on regulating effort or target catch. These tools comprise both static and dynamic area‐based approaches to include gear limitations, closed areas and bycatch limits. There are increasing calls for additional area‐based interventions, particularly expansion of marine protected areas, with many now advocating closing 30% of the oceans to fishing. In this paper, we review the objectives, methods and successes of area‐based management of blue water fisheries across objectives related to food production and environmental, social and economic impacts. We also consider the methods used to evaluate the performance of area‐based regulations and provide a summary of the relative quality of evidence from alternative evaluation approaches. We found that few area‐based approaches have been rigorously evaluated, and that it is often difficult to obtain requisite observational data to define a counterfactual to infer any causal effect for such evaluation. Management agencies have been relatively successful at maintaining important commercial species at or near their target abundance, but success at meeting ecological or social goals is less clear. The high mobility of both target and bycatch species generally reduces the effectiveness of area‐based management, and shifting distributions due to climate change suggest that adaptive rather than static approaches will be preferred. We prioritize research and management actions that would make area‐based management more effective.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Lunar feldspathic meteorite Dhofar 081: Petrochemical constraints on petrogenesis - Dwijesh Ray; Saumitra Misra; David R Nelson (Journal of Earth System Science, 2021)

Large‐scale genome sampling reveals unique immunity and metabolic adaptations in bats - Diana D. Moreno Santillán; Tanya M. Lama; Yocelyn T. Gutierrez Guerrero; Alexis M. Brown; Paul Donat; Huabin Zhao; Stephen J. Rossiter; Laurel R. Yohe; Joshua H. Potter; Emma C. Teeling; Sonja C. Vernes; Kalina T. J. Davies; et al. (Molecular Ecology, 2021)
Comprising more than 1,400 species, bats possess adaptations unique among mammals including powered flight, unexpected longevity, and extraordinary immunity. Some of the molecular mechanisms underlying these unique adaptations includes DNA repair, metabolism and immunity. However, analyses have been limited to a few divergent lineages, reducing the scope of inferences on gene family evolution across the Order Chiroptera. We conducted an exhaustive comparative genomic study of 37 bat species, one generated in this study, encompassing a large number of lineages, with a particular emphasis on multi‐gene family evolution across immune and metabolic genes. In agreement with previous analyses, we found lineage‐specific expansions of the APOBEC3 and MHC‐I gene families, and loss of the proinflammatory PYHIN gene family. We inferred more than 1,000 gene losses unique to bats, including genes involved in the regulation of inflammasome pathways such as epithelial defence receptors, the natural killer gene complex and the interferon‐gamma induced pathway. Gene set enrichment analyses revealed genes lost in bats are involved in defence response against pathogen‐associated molecular patterns and damage‐associated molecular patterns. Gene family evolution and selection analyses indicate bats have evolved fundamental functional differences compared to other mammals in both innate and adaptive immune system, with the potential to enhance antiviral immune response while dampening inflammatory signalling. In addition, metabolic genes have experienced repeated expansions related to convergent shifts to plant‐based diets. Our analyses support the hypothesis that, in tandem with flight, ancestral bats had evolved a unique set of immune adaptations whose functional implications remain to be explored.

Novel Metabolites as Potential Indicators of Ischemic Infarction Volume: a Pilot Study - Evgeny V. Sidorov; Cynthia Bejar; Chao Xu; Bappaditya Ray; David Gordon; Juliane Chainakul; Dharambir K. Sanghera (Translational Stroke Research, 2021)

The Path to an Ecosystem Approach for Forage Fish Management: A Case Study of Atlantic Menhaden - Kristen A. Anstead; Katie Drew; David Chagaris; Amy M. Schueller; Jason E. McNamee; Andre Buchheister; Geneviève Nesslage; Jim H. Uphoff Jr.; Michael J. Wilberg; Alexei Sharov; Micah J. Dean; Jeffrey Brust; et al. (Frontiers in Marine Science, 2021)
Atlantic menhaden ( Brevoortia tyrannus ) support the largest fishery by volume on the United States East Coast, while also playing an important role as a forage species. Managers’ and stakeholders’ increasing concerns about the impact of Atlantic menhaden harvest on ecosystem processes led to an evolution in the assessment and management of this species from a purely single-species approach to an ecosystem approach. The first coastwide stock assessment of Atlantic menhaden for management used a single-species virtual population analysis (VPA). Subsequent assessments used a forward projecting statistical catch-at-age framework that incorporated estimates of predation mortality from a multispecies VPA while analytical efforts continued toward the development of ecosystem models and explicit ecological reference points (ERPs) for Atlantic menhaden. As an interim step while ecosystem models were being developed, a series of ad hoc measures to preserve Atlantic menhaden biomass for predators were used by managers. In August 2020, the Atlantic States Marine Fisheries Commission formally adopted an ecological modeling framework as a tool to set reference points and harvest limits for the Atlantic menhaden that considers their role as a forage fish. This is the first example of a quantitative ecosystem approach to setting reference points on the United States Atlantic Coast and it represents a significant advance for forage fish management. This case study reviews the history of Atlantic menhaden stock assessments and management, outlines the progress on the current implementation of ERPs for this species, and highlights future research and management needs to improve and expand ecosystem-based fisheries management.

Life cycle assessment comparison of wooden and plastic pallets in the grocery industry - Sebastian K. Anil; Junfeng Ma; Gül E. Kremer; Charles David Ray; Shirin M. Shahidi (Journal of Industrial Ecology, 2020)
Wooden and plastic pallets are used extensively in global trade to transport finished goods and products. This article compares the life cycle performance of treated wooden and plastic pallets through a detailed cradle‐to‐grave life cycle assessment (LCA), and conducts an analysis of the various phytosanitary treatments. The LCA investigates and evaluates the environmental impacts due to the resources consumed and emissions of the product throughout its life cycle. The environmental impacts of the pallets are compared on a one‐trip basis and a 100,000‐trips basis. Impact categories are chosen with respect to environmental concerns. The results show that on a one‐trip basis, wooden pallets with conventional and radio frequency (RF) heat treatment incur an overall carbon footprint of 71.8% and 80.3% lower, respectively, than plastic pallets during their life cycle; and in comparison with wooden pallets treated with methyl bromide fumigation, they incur 20% and 30% less overall carbon footprint. Theoretical calculations of the resource consumption and emissions of RF treatment of pallets suggest that dielectric technology may provide a lower‐carbon alternative to both current ISPM 15‐approved treatments and to plastic pallets. Methyl bromide fumigation (15.95 kg CO 2 equivalent [eq.]) has a larger carbon footprint than conventional heat treatment (12.69 kg CO 2 eq.) of pallets. For the 100,000‐trips basis, the differences are even more significant. The results recommend that wooden pallets are more environmentally friendly than plastic pallets, and conventional and RF heat treatment for wooden pallets is more sustainable than methyl bromide fumigation treatment.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Atmospheric histories, growth rates and solubilities in seawater and other natural waters of the potential transient tracers HCFC-22, HCFC-141b, HCFC-142b, HFC-134a, HFC-125, HFC-23, PFC-14 and PFC-116 - Pingyang Li; Jens Mühle; Stephen A. Montzka; David E. Oram; Benjamin R. Miller; Ray F. Weiss; Paul J. Fraser; Toste Tanhua (Ocean Science, 2019)
We present consistent annual mean atmospheric histories and growth rates for the mainly anthropogenic halogenated compounds HCFC-22, HCFC-141b, HCFC-142b, HFC-134a, HFC-125, HFC-23, PFC-14 and PFC-116, which are all potentially useful oceanic transient tracers (tracers of water transport within the ocean), for the Northern and Southern Hemisphere with the aim of providing input histories of these compounds for the equilibrium between the atmosphere and surface ocean. We use observations of these halogenated compounds made by the Advanced Global Atmospheric Gases Experiment (AGAGE), the Scripps Institution of Oceanography (SIO), the Commonwealth Scientific and Industrial Research Organization (CSIRO), the National Oceanic and Atmospheric Administration (NOAA) and the University of East Anglia (UEA). Prior to the direct observational record, we use archived air measurements, firn air measurements and published model calculations to estimate the atmospheric mole fraction histories. The results show that the atmospheric mole fractions for each species, except HCFC-141b and HCFC-142b, have been increasing since they were initially produced. Recently, the atmospheric growth rates have been decreasing for the HCFCs (HCFC-22, HCFC-141b and HCFC-142b), increasing for the HFCs (HFC-134a, HFC-125, HFC-23) and stable with little fluctuation for the PFCs (PFC-14 and PFC-116) investigated here. The atmospheric histories (source functions) and natural background mole fractions show that HCFC-22, HCFC-141b, HCFC-142b, HFC-134a, HFC-125 and HFC-23 have the potential to be oceanic transient tracers for the next few decades only because of the recently imposed bans on production and consumption. When the atmospheric histories of the compounds are not monotonically changing, the equilibrium atmospheric mole fraction (and ultimately the age associated with that mole fraction) calculated from their concentration in the ocean is not unique, reducing their potential as transient tracers. Moreover, HFCs have potential to be oceanic transient tracers for a longer period in the future than HCFCs as the growth rates of HFCs are increasing and those of HCFCs are decreasing in the background atmosphere. PFC-14 and PFC-116, however, have the potential to be tracers for longer periods into the future due to their extremely long lifetimes, steady atmospheric growth rates and no explicit ban on their emissions. In this work, we also derive solubility functions for HCFC-22, HCFC-141b, HCFC-142b, HFC-134a, HFC-125, HFC-23, PFC-14 and PFC-116 in water and seawater to facilitate their use as oceanic transient tracers. These functions are based on the Clark–Glew–Weiss (CGW) water solubility function fit and salting-out coefficients estimated by the poly-parameter linear free-energy relationships (pp-LFERs). Here we also provide three methods of seawater solubility estimation for more compounds. Even though our intention is for application in oceanic research, the work described in this paper is potentially useful for tracer studies in a wide range of natural waters, including freshwater and saline lakes, and, for the more stable compounds, groundwaters.

Coated-Platelet Trends Predict Short-Term Clinical OutcomeAfter Subarachnoid Hemorrhage - Bappaditya Ray; Vijay M. Pandav; Eleanor A. Mathews; David M. Thompson; Lance Ford; Lori K. Yearout; Bradley N. Bohnstedt; Shuchi Chaudhary; George L. Dale; Calin I. Prodan (Translational Stroke Research, 2018)

A mathematical model of recurrent spreading depolarizations - Cameron Conte; Ray Lee; Monica Sarkar; David Terman (Journal of Computational Neuroscience, 2018)

Mammalian transposable elements and their impacts on genome evolution - Roy N. Platt; Michael W. Vandewege; David A. Ray (Chromosome Research, 2018)

Replacement of a unique population of newts (Taricha granulosa mazamae) by introduced signal crayfish (Pacifastacus leniusculus) in Crater Lake, Oregon - Scott F. Girdner; Andrew M. Ray; Mark W. Buktenica; David K. Hering; Jeremy A. Mack; John W. Umek (Biological Invasions, 2018)

Transcriptomic changes in Echinochloa colona in response to treatment with the herbicide imazamox - Alice A. Wright; Rajkumar Sasidharan; Liisa Koski; Marianela Rodriguez-Carres; Daniel G. Peterson; Vijay K. Nandula; Jeffery D. Ray; Jason A. Bond; David R. Shaw (Planta, 2018)

Decadal declines in avian herbivore reproduction: density‐dependent nutrition and phenological mismatch in the Arctic - Megan V. Ross; Ray T. Alisauskas; David C. Douglas; Dana K. Kellett (Ecology, 2017)
A full understanding of population dynamics depends not only on estimation of mechanistic contributions of recruitment and survival, but also knowledge about the ecological processes that drive each of these vital rates. The process of recruitment in particular may be protracted over several years, and can depend on numerous ecological complexities until sexually mature adulthood is attained. We addressed long‐term declines (23 breeding seasons, 1992–2014) in the per capita production of young by both Ross's Geese ( Chen rossii ) and Lesser Snow Geese ( Chen caerulescens caerulescens ) nesting at Karrak Lake in Canada's central Arctic. During this period, there was a contemporaneous increase from 0.4 to 1.1 million adults nesting at this colony. We evaluated whether (1) density‐dependent nutritional deficiencies of pre‐breeding females or (2) phenological mismatch between peak gosling hatch and peak forage quality, inferred from NDVI on the brood‐rearing areas, may have been behind decadal declines in the per capita production of goslings. We found that, in years when pre‐breeding females arrived to the nesting grounds with diminished nutrient reserves, the proportional composition of young during brood‐rearing was reduced for both species. Furthermore, increased mismatch between peak gosling hatch and peak forage quality contributed additively to further declines in gosling production, in addition to declines caused by delayed nesting with associated subsequent negative effects on clutch size and nest success. The degree of mismatch increased over the course of our study because of advanced vegetation phenology without a corresponding advance in Goose nesting phenology. Vegetation phenology was significantly earlier in years with warm surface air temperatures measured in spring (i.e., 25 May–30 June). We suggest that both increased phenological mismatch and reduced nutritional condition of arriving females were behind declines in population‐level recruitment, leading to the recent attenuation in population growth of Snow Geese.

Evaluating species-specific changes in hydrologic regimes: an iterative approach for salmonids in the Greater Yellowstone Area (USA) - Robert Al-Chokhachy; Adam J. Sepulveda; Andrew M. Ray; David P. Thoma; Michael T. Tercek (Reviews in Fish Biology and Fisheries, 2017)

Ascospore release and discharge distances of Fusarium graminearum under controlled temperature and relative humidity - Ray F. David; Linsey C. Marr; David G. Schmale (European Journal of Plant Pathology, 2016)

Prioritization of knowledge‐needs to achieve best practices for bottom trawling in relation to seabed habitats - Michel J Kaiser; Ray Hilborn; Simon Jennings; Ricky Amaroso; Michael Andersen; Kris Balliet; Eric Barratt; Odd A Bergstad; Stephen Bishop; Jodi L Bostrom; Catherine Boyd; Eduardo A Bruce; et al. (Fish and Fisheries, 2016)
Management and technical approaches that achieve a sustainable level of fish production while at the same time minimizing or limiting the wider ecological effects caused through fishing gear contact with the seabed might be considered to be ‘best practice’. To identify future knowledge‐needs that would help to support a transition towards the adoption of best practices for trawling, a prioritization exercise was undertaken with a group of 39 practitioners from the seafood industry and management, and 13 research scientists who have an active research interest in bottom‐trawl and dredge fisheries. A list of 108 knowledge‐needs related to trawl and dredge fisheries was developed in conjunction with an ‘expert task force’. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge‐need. The top 25 knowledge‐needs are presented, as scored separately by practitioners and scientists. There was considerable consistency in the priorities identified by these two groups. The top priority knowledge‐need to improve current understanding on the distribution and extent of different habitat types also reinforced the concomitant need for the provision and access to data on the spatial and temporal distribution of all forms of towed bottom‐fishing activities. Many of the other top 25 knowledge‐needs concerned the evaluation of different management approaches or implementation of different fishing practices, particularly those that explore trade‐offs between effects of bottom trawling on biodiversity and ecosystem services and the benefits of fish production as food.

Identification of meteorological predictors of Fusarium graminearum ascospore release using correlation and causality analyses - Ray F. David; Amir E. BozorgMagham; David G. Schmale; Shane D. Ross; Linsey C. Marr (European Journal of Plant Pathology, 2016)

Science–policy processes for transboundary water governance - Derek Armitage; Rob C. de Loë; Michelle Morris; Tom W. D. Edwards; Andrea K. Gerlak; Roland I. Hall; Dave Huitema; Ray Ison; David Livingstone; Glen MacDonald; Naho Mirumachi; Ryan Plummer; et al. (Ambio, 2015)

Comparison of low-carbon pathways for California - Geoffrey M. Morrison; Sonia Yeh; Anthony R. Eggert; Christopher Yang; James H. Nelson; Jeffery B. Greenblatt; Raphael Isaac; Mark Z. Jacobson; Josiah Johnston; Daniel M. Kammen; Ana Mileva; Jack Moore; et al. (Climatic Change, 2015)

Methane and nitrous oxide emissions from rice and maize production in diversified rice cropping systems - Sebastian Weller; David Kraus; Kevin Ray P. Ayag; Reiner Wassmann; M. C. R. Alberto; Klaus Butterbach-Bahl; Ralf Kiese (Nutrient Cycling in Agroecosystems, 2015)

Shift work and breast cancer among women textile workers in Shanghai, China - Wenjin Li; Roberta M. Ray; David B. Thomas; Scott Davis; Michael Yost; Norman Breslow; Dao Li Gao; E. Dawn Fitzgibbons; Janice E. Camp; Eva Wong; Karen J. Wernli; Harvey Checkoway (Cancer Causes & Control, 2015)

The energy‐conserving electron transfer system used by D esulfovibrio alaskensis strain G 20 during pyruvate fermentation involves reduction of endogenously formed fumarate and cytoplasmic and membrane‐bound complexes, Hdr‐Flox and Rnf - Birte Meyer; Jennifer V. Kuehl; Morgan N. Price; Jayashree Ray; Adam M. Deutschbauer; Adam P. Arkin; David A. Stahl (Environmental Microbiology, 2014)
Summary The adaptation capability of D esulfovibrio to natural fluctuations in electron acceptor availability was evaluated by studying D esulfovibrio alaskensis strain G 20 under varying respiratory, fermentative and methanogenic coculture conditions in chemostats. Transition from lactate to pyruvate in coculture resulted in a dramatic shift in the population structure and closer interspecies cell‐to‐cell interactions. Lower methane production rates in coculture than predicted from pyruvate input was attributed to redirection of electron flow to fumarate reduction. Without a methanogenic partner, accumulation of H 2 and formate resulted in greater succinate production. Comparative transcript and gene fitness analysis in concert with physiological data of G 20 wildtype and mutants demonstrated that pyruvate fermentation involves respiration of cytoplasmically formed fumarate using cytoplasmic and membrane‐bound energy‐conserving complexes, Rnf , Hdr‐Flox ‐1 and Hmc. At the low H 2 /formate levels maintained in coculture, Rnf likely functions as proton‐pumping ferredoxin (Fd) : type‐I cytochrome c oxidoreductase, which transitions to a proton‐pumping Fd red : nicotinamide adenine dinucleotide ( NAD + ) oxidoreductase at high H 2 /formate levels during fermentation in monoculture. Hdr‐Flox ‐1 is postulated to recycle Fd red via a flavin‐based electron bifurcation involving NADH , Fd ox and the thiol/disulphide‐containing DsrC . In a menaquinone ( MQ )‐based electron confurcation reaction, the high‐molecular‐weight cytochrome‐c 3 complex, Hmc , is proposed to then couple DsrC red and periplasmic H 2 /formate oxidation using the MQ pool to fuel a membrane‐bound fumarate reductase.

Trading in snails: plant nurseries as transport hubs for non-native species - Elizabeth A. Bergey; Laura L. Figueroa; Charles M. Mather; Rebekah J. Martin; Eric J. Ray; Jobin T. Kurien; David R. Westrop; Phushewan Suriyawong (Biological Invasions, 2014)

Neighborhoods have little effect on fungal attack or insect predation of developing seeds in a grassland biodiversity experiment - Noelle G. Beckman; Ray Dybzinski; G. David Tilman (Oecologia, 2014)

Iron cycling at corroding carbon steel surfaces - Jason S. Lee; Joyce M. McBeth; Richard I. Ray; Brenda J. Little; David Emerson (Biofouling, 2013)

Resource limitation in a competitive context determines complex plant responses to experimental resource additions - Caroline E. Farrior; David Tilman; Ray Dybzinski; Peter B. Reich; Simon A. Levin; Stephen W. Pacala (Ecology, 2013)
Almost all models of plant resource limitation are grounded in either one or both of two simple conceptual models: Liebig's Minimum Hypothesis (LMH), the idea that plants are limited by the resource in shortest supply, and the Multiple Limitation Hypothesis (MLH), the idea that plants should adjust to their environment so that all essential resources are equally limiting. Despite the differences in their predictions, experiments have so far failed to discriminate between them. In a simple factorial nitrogen and water addition experiment in a Minnesota grassland, we observed shifts in allocation that, as in previous studies, are not all explained by a single theory. We found that leaf biomass responded positively to nitrogen additions but did not respond to water additions. We found that fine‐root biomass increased in response to water additions, but only at low nitrogen levels, and that fine‐root biomass decreased in response to nitrogen additions, but only at high water levels. To understand these responses we built a physiologically based model of plant competition for water, nitrogen, and space to predict plant allocation to fine roots and leaves. Critically, we include in our model the inherent variability of soil moisture and treat light, water, and nitrogen as resources with distinct mechanistic roles. Experimental results showed that plants were nitrogen and water limited. The model explains the experimental results, under conditions of co‐limitation, as follows. Foliage increases with nitrogen additions but not water additions because leaf construction is constrained by nitrogen uptake. When water is added, plants spend a larger fraction of the growing season limited by light (and effectively nitrogen) than by water. Thus, water additions cause fine‐root biomass to increase because of the increased importance of nitrogen limitation. The response of fine‐root biomass to water additions decreases with nitrogen additions because these additions reduce nitrogen limitation. In general, our results are explained by sequential resource limitation. The rate of carbon assimilation may be limited by a single resource at any one moment, but the identity of the limiting resource(s) changes throughout the growing season.

Reproductive factors and risk of lung cancer in female textile workers in Shanghai, China - Lisa G. Gallagher; Karin A. Rosenblatt; Roberta M. Ray; Wenjin Li; Dao L. Gao; Katie M. Applebaum; Harvey Checkoway; David B. Thomas (Cancer Causes & Control, 2013)

Seed and microsite limitation in a late-successional old field: the effects of water, adults, litter, and small mammals on seeds and seedlings - Ray Dybzinski; David Tilman (Plant Ecology, 2012)

Water Dynamics in Fresh and Frozen Yeasted Dough - Simon M. Loveday; Victor T. Huang; David S. Reid; Ray J. Winger (Critical Reviews in Food Science and Nutrition, 2012)

Strategies to mitigate aliasing of loading signals while estimating GPS frame parameters - Xavier Collilieux; Tonie van Dam; Jim Ray; David Coulot; Laurent Métivier; Zuheir Altamimi (Journal of Geodesy, 2012)

Risk of lung cancer in relation to contiguous windows of endotoxin exposure among female textile workers in Shanghai - Ilir Agalliu; Sadie Costello; Katie M. Applebaum; Roberta M. Ray; George Astrakianakis; Dao Li Gao; David B. Thomas; Harvey Checkoway; Ellen A. Eisen (Cancer Causes & Control, 2011)

Carbon Inputs and Water Uptake in Deep Soils of an Eastern Amazon Forest - Eric Davidson; Paul A. Lefebvre; Paulo M. Brando; David M. Ray; Susan E. Trumbore; Luis A. Solorzano; Joice N. Ferreira; Mercedes M. da C. Bustamante; Daniel C. Nepstad (Forest Science, 2011)
Rooting depth affects soil profiles of water uptake and carbon inputs. Here we explore the importance of deep roots in a mature tropical forest of eastern Amazonia, where a throughfall exclusion experiment was conducted to test the resilience of the forest to experimentally induced drought. We hypothesized that soil water depletion occurred below the depth previously measured by sensors in 11-m-deep soil pits and that only a small root biomass is necessary to affect water uptake and the isotopic signature of soil CO2. A noninvasive electrical profiling method demonstrated greater depletion of soil water in the 11-18 m depth increment in the exclusion plot compared with the control plot by the end of the 3rd year of the experiment. A fine root biomass of only 0.1 g/cm3 measured at 3-6 m was sufficient for soil water drawdown and for imparting an isotopic signature of modern soil 14CO2 in both plots. A soil 13CO2 profile indicated drought stress in the exclusion plot. Fine root inputs of organic C to deep soils are small with respect to the carbon dynamics of the forest, but the deep rooting habit clearly affects the ecosystem water balance and profiles of soil CO2.

Rhyolites at Kerlingarfjöll, Iceland: the evolution and lifespan of silicic central volcanoes - Stephanie Flude; David W. McGarvie; Ray Burgess; Andrew G. Tindle (Bulletin of Volcanology, 2010)

Complete preservation of ophiolite suite from south Andaman, India: A mineral-chemical perspective - Abhishek Saha; Avik Dhang; Jyotisankar Ray; Suvankar Chakraborty; David Moecher (Journal of Earth System Science, 2010)

Respiratory muscle training reduces the work of breathing at depth - Andrew D. Ray; David R. Pendergast; Claes E. G. Lundgren (European Journal of Applied Physiology, 2010)

Carbon storage of bottomland hardwood afforestation in the Lower Mississippi Valley, USA - David T. Shoch; Gary Kaster; Aaron Hohl; Ray Souter (Wetlands, 2009)

Oral contraceptives and the risk of all cancers combined and site-specific cancers in Shanghai - Karin A. Rosenblatt; Dao L. Gao; Roberta M. Ray; Zakia C. Nelson; Karen J. Wernli; Wenjin Li; David B. Thomas (Cancer Causes & Control, 2009)

The Turbulent Lagrangian Time Scale in Forest Canopies Constrained by Fluxes, Concentrations and Source Distributions - Vanessa Haverd; Ray Leuning; David Griffith; Eva van Gorsel; Matthias Cuntz (Boundary-Layer Meteorology, 2009)

Mitigating Climate Change with Managed Forests: Balancing Expectations, Opportunity, and Risk - David G. Ray; Robert S. Seymour; Neal A. Scott; William S. Keeton (Journal of Forestry, 2009)

Comparison of Cytochrome P450 Genes from Six Plant Genomes - David R. Nelson; Ray Ming; Maqsudul Alam; Mary A. Schuler (Tropical Plant Biology, 2008)

Soil fertility increases with plant species diversity in a long-term biodiversity experiment - Ray Dybzinski; Joseph E. Fargione; Donald R. Zak; Dario Fornara; David Tilman (Oecologia, 2008)

Replication of association between ELAVL4 and Parkinson disease: the GenePD study - Anita L. DeStefano; Jeanne Latourelle; Mark F. Lew; Oksana Suchowersky; Christine Klein; Lawrence I. Golbe; Margery H. Mark; John H. Growdon; G. Fredrick Wooten; Ray Watts; Mark Guttman; Brad A. Racette; et al. (Human Genetics, 2008)

Age and microvascular responses to knee extensor exercise in women - Beth A. Parker; Sandra L. Smithmyer; Samuel J. Ridout; Chester A. Ray; David N. Proctor (European Journal of Applied Physiology, 2008)

Leaf Nutrient Concentrations and Timber Productivity in the Dry Sclerophyll Forests of South-East Queensland, Australia: Implications for Arboreal Marsupials - Kevin Ray Wormington; David Lamb; Hamish Ian McCallum; Damien John Moloney (Forest Science, 2007)
The species richness and abundance of arboreal marsupials are positively related to the proportion of total stand basal area occupied by Corymbia citriodora ssp. variegata and tree height in South-East Queensland and have been related to nutrient availability and productivity in other parts of Australia. The objectives of this study were to assess the relationships of stand basal area occupied by C. citriodora and tree height, and the available nutrients and productivity in the dry sclerophyll forests of South-East Queensland. Leaf nutrient analysis of seven species of trees in South-East Queensland showed that the percentage by weight of phosphorus in leaves increased with the proportion of the total stand basal area of C. citriodora. This rate of increase was greater for C. citriodora than other species, indicating that C. citriodora may be more competitive on soils with greater available phosphorus. C. citriodora leaves also contained higher concentrations of nitrogen and potassium than the other tree species on multispecies sites. Timber productivity was greater at the sites where trees were taller, and tree height was positively correlated to the proportion of total stand basal area of C. citriodora and rainfall but was negatively correlated to the slope. These findings indicate that the most used habitat by arboreal marsupials in the dry sclerophyll forests of South-East Queensland (i.e., taller forests with a high proportion of the stand basal area occupied by C. citriodora) had higher concentrations of foliar nutrients and were more productive than less used habitats.

Actin-filament-dependent remodeling of the vacuole in cultured mesophyll protoplasts - Michael B. Sheahan; Ray J. Rose; David W. McCurdy (Protoplasma, 2007)

SINEs of progress: Mobile element applications to molecular ecology - DAVID A. RAY (Molecular Ecology, 2007)
Mobile elements represent a unique and under‐utilized set of tools for molecular ecologists. They are essentially homoplasy‐free characters with the ability to be genotyped in a simple and efficient manner. Interpretation of the data generated using mobile elements can be simple compared to other genetic markers. They exist in a wide variety of taxa and are useful over a wide selection of temporal ranges within those taxa. Furthermore, their mode of evolution instills them with another advantage over other types of multilocus genotype data: the ability to determine loci applicable to a range of time spans in the history of a taxon. In this review, I discuss the application of mobile element markers, especially short interspersed elements (SINEs), to phylogenetic and population data, with an emphasis on potential applications to molecular ecology.

Induced abortions and the risk of all cancers combined and site-specific cancers in Shanghai - Karin A. Rosenblatt; Dao L. Gao; Roberta M. Ray; Michelle R. Rowland; Zakia C. Nelson; Karen J. Wernli; Wenjin Li; David B. Thomas (Cancer Causes & Control, 2006)

New global positioning system reference station in Brazil - Jim Ray; David Crump; Miranda Chin (GPS Solutions, 2006)

Effects of partial throughfall exclusion on the phenology of Coussarea racemosa (Rubiaceae) in an east-central Amazon rainforest - Paulo Brando; David Ray; Daniel Nepstad; Gina Cardinot; Lisa M. Curran; Rafael Oliveira (Oecologia, 2006)

Menstrual and reproductive factors in relation to risk of endometrial cancer in Chinese women - Karen J. Wernli; Roberta M. Ray; Dao Li Gao; Anneclaire J. De Roos; Harvey Checkoway; David B. Thomas (Cancer Causes & Control, 2006)

Influence of menstrual cycle phase on pulmonary function in asthmatic athletes - Kristin I. Stanford; Timothy D. Mickleborough; Shahla Ray; Martin R. Lindley; David M. Koceja; Joel M. Stager (European Journal of Applied Physiology, 2006)

Dynamics of fine root carbon in Amazonian tropical ecosystems and the contribution of roots to soil respiration - Susan Trumbore; Enir Salazar Da Costa; Daniel C. Nepstad; Plínio Barbosa De Camargo; Luiz A. Martinelli; David Ray; Teresa Restom; Whendee Silver (Global Change Biology, 2006)
Radiocarbon ( 14 C) provides a measure of the mean age of carbon (C) in roots, or the time elapsed since the C making up root tissues was fixed from the atmosphere. Radiocarbon signatures of live and dead fine ( 40 years). Measurements of 14 C in the structural tissues of roots known to have grown during 2002 demonstrate that new roots are constructed from recent ( 14 C values in live roots most likely indicate the mean lifetime of the root rather than the isotopic signature of inherited C or C taken up from the soil. Estimates of the mean residence time of C in forest fine roots (inventory divided by loss rate) are substantially shorter (1–3 years) than the age of standing fine root C stocks obtained from radiocarbon (4–11 years). By assuming positively skewed distributions for root ages, we can effectively decouple the mean age of C in live fine roots (measured using 14 C) from the rate of C flow through the live root pool, and resolve these apparently disparate estimates of root C dynamics. Explaining the 14 C values in soil pore space CO 2 , in addition, requires that a portion of the decomposing roots be cycled through soil organic matter pools with decadal turnover time.

Temporal Changes between Ecological Regimes in a Range of Primary and Secondary Salinised Wetlands - Karin Strehlow; Jenny Davis; Lien Sim; Jane Chambers; Stuart Halse; David Hamilton; Pierre Horwitz; Arthur McComb; Ray Froend (Hydrobiologia, 2005)

Comments on the paper ?Spatial and temporal variability in excessive soil phosphorus levels in Eastern North Carolina? by Cahoon and Ensign - David H. Hardy; Richard C. Reich; M. Ray Tucker (Nutrient Cycling in Agroecosystems, 2005)

Comments on the paper ?Spatial and temporal variability in excessive soil phosphorus levels in eastern North Carolina? by Cahoon and Ensign - David H. Hardy; Richard C. Reich; M. Ray Tucker (Nutrient Cycling in Agroecosystems, 2004)

Low Levels of Nucleotide Diversity in Crocodylus moreletii and Evidence of Hybridization with C. acutus - David A. Ray; Jennifer A. Dever; Steven G. Platt; Thomas R. Rainwater; Adam G. Finger; Scott T. McMurry; Mark A. Batzer; Brady Barr; Peter J. Stafford; Jenna McKnight; Llewellyn D. Densmore (Conservation Genetics, 2004)

Amazon drought and its implications for forest flammability and tree growth: a basin‐wide analysis - Daniel Nepstad; Paul Lefebvre; Urbano Lopes da Silva; Javier Tomasella; Peter Schlesinger; Luiz Solórzano; Paulo Moutinho; David Ray; José Guerreira Benito (Global Change Biology, 2004)
Severe drought in moist tropical forests provokes large carbon emissions by increasing forest flammability and tree mortality, and by suppressing tree growth. The frequency and severity of drought in the tropics may increase through stronger El Niño Southern Oscillation (ENSO) episodes, global warming, and rainfall inhibition by land use change. However, little is known about the spatial and temporal patterns of drought in moist tropical forests, and the complex relationships between patterns of drought and forest fire regimes, tree mortality, and productivity. We present a simple geographic information system soil water balance model, called RisQue (Risco de Queimada – Fire Risk) for the Amazon basin that we use to conduct an analysis of these patterns for 1996–2001. RisQue features a map of maximum plant‐available soil water (PAW max ) developed using 1565 soil texture profiles and empirical relationships between soil texture and critical soil water parameters. PAW is depleted by monthly evapotranspiration (ET) fields estimated using the Penman–Monteith equation and satellite‐derived radiation inputs and recharged by monthly rain fields estimated from 266 meteorological stations. Modeled PAW to 10 m depth (PAW 10 m ) was similar to field measurements made in two Amazon forests. During the severe drought of 2001, PAW 10 m fell to below 25% of PAW max in 31% of the region's forests and fell below 50% PAW max in half of the forests. Field measurements and experimental forest fires indicate that soil moisture depletion below 25% PAW max corresponds to a reduction in leaf area index of approximately 25%, increasing forest flammability. Hence, approximately one‐third of Amazon forests became susceptible to fire during the 2001 ENSO period. Field measurements also suggest that the ENSO drought of 2001 reduced carbon storage by approximately 0.2 Pg relative to years without severe soil moisture deficits. RisQue is sensitive to spin‐up time, rooting depth, and errors in ET estimates. Improvements in our ability to accurately model soil moisture content of Amazon forests will depend upon better understanding of forest rooting depths, which can extend to beyond 15 m. RisQue provides a tool for early detection of forest fire risk.

Improvement in hydroxy fatty acid seed oil content and other traits from interspecific hybrids of three Lesquerella species: Lesquerella fendleri, L. pallida, and L. lindheimeri - David A. Dierig; Pernell M. Tomasi; Andrew M. Salywon; Dennis T. Ray (Euphytica, 2004)

Controls of fluid chemistry and complexation on rare-earth element contents of anhydrite from the Pacmanus subseafloor hydrothermal system, Manus Basin, Papua New Guinea - Wolfgang Bach; Stephen Roberts; David A. Vanko; Ray A. Binns; Chris J. Yeats; Paul R. Craddock; Susan E. Humphris (Mineralium Deposita, 2003)

Enhancement of Solubility and Bioavailability of β-Lapachone Using Cyclodextrin Inclusion Complexes - Norased Nasongkla; Andy F. Wiedmann; Andrew Bruening; Meghan Beman; Dale Ray; William G. Bornmann; David A. Boothman; Jinming Gao (Pharmaceutical Research, 2003)

Development of gypsy moth larvae feeding on red maple saplings at elevated CO 2 and temperature - Ray S. Williams; David E. Lincoln; Richard J. Norby (Oecologia, 2003)

Developmental toxicity of pyrethroids - Bala Muhammad; Richard Verschoyle; David Ray (Archives of Toxicology, 2003)

Dietary risk factors for invasive and in-situ cervical carcinomas in Bangkok, Thailand - Jackilen Shannon; David B. Thomas; Roberta M. Ray; Mark Kestin; Amorn Koetsawang; Suporn Koetsawang; Kamolthip Chitnarong; Nancy Kiviat; Jane Kuypers (Cancer Causes & Control, 2002)

Risk factors for progression of squamous cell cervical carcinoma in-situ to invasive cervical cancer: results of a multinational study - David B. Thomas; Roberta M. Ray; Qin Qin (Cancer Causes & Control, 2002)

Habitat Requirements for the Conservation of Arboreal Marsupials in Dry Sclerophyll Forests of Southeast Queensland, Australia - Kevin Ray Wormington; David Lamb; Hamish Ian McCallum; Damien John Moloney (Forest Science, 2002)
The habitat requirements of arboreal marsupials were investigated in the dry sclerophyll forests of southeast Queensland, Australia. Species richness and abundance of arboreal marsupials was correlated to the proportion of total stand basal area occupied by lemon-scented gum (Corymbia citriodora), the height of the tallest trees, and density of hollow-bearing trees. The first two factors suggested that the most productive forests were also the most suitable habitats for arboreal marsupials. Importantly, the number of hollow-bearing trees was a significant factor in determining species richness and abundance of arboreal marsupials in this study, with the maximum number of species reached at sites containing≥4 hollow-bearing trees/ha, and maximum abundance occurring at sites with≥6 hollow-bearing trees/ha. The proportion of C. citriodora was significant for the presence of the common brushtail possum (Trichosurus vulpecula), greater glider (Petauroides volans), and the yellow-bellied glider (Petaurus australis), while understory Acacia sp. density was important for the presence of the sugar glider (Petaurus breviceps). The yellow-bellied glider was also affected by two other variables: the density of hollow-bearing trees >50 cm diameter at breast height (dbh), and the time since the last logging. Current “Codes of Practice” regulating the density of hollow-bearing trees and silvicultural practices in state-owned timber production forests appear to provide adequate protection for arboreal marsupials, but the recently introduced increase in timber extraction rates within state forests may be detrimental to the animals. Also, protective prescriptions do not apply to the privately owned and leasehold estates, which contain the majority of the dry sclerophyll forests in southeast Queensland. FOR. SCI. 48(2):217–227.

Actin and Flagellin May Have an N-Terminal Relationship - Ray J. Harris; David Elder (Journal of Molecular Evolution, 2002)

Non-litter effects of elevated CO2 on forest floor microarthropod abundances - Randi A. Hansen; Ray S. Williams; David C. Degenhardt; David E. Lincoln (Plant and Soil, 2001)

Ribozyme Relationships: The Hammerhead, Hepatitis Delta, and Hairpin Ribozymes Have a Common Origin - Ray J. Harris; David Elder (Journal of Molecular Evolution, 2000)

Effects of elevated CO 2 and temperature‐grown red and sugar maple on gypsy moth performance - Ray S. Williams; Richard J. Norby; David E. Lincoln (Global Change Biology, 2000)
Summary Few studies have investigated how tree species grown under elevated CO 2 and elevated temperature alter the performance of leaf‐feeding insects. The indirect effects of an elevated CO 2 concentration and temperature on leaf phytochemistry, along with potential direct effects on insect growth and consumption, may independently or interactively affect insects. To investigate this, we bagged larvae of the gypsy moth on leaves of red and sugar maple growing in open‐top chambers in four CO 2 /temperature treatment combinations: (i) ambient temperature, ambient CO 2 ; (ii) ambient temperature, elevated CO 2 (+ 300 μL L −1 CO 2 ); (iii) elevated temperature (+ 3.5°C), ambient CO 2 ; and (iv) elevated temperature, elevated CO 2 . For both tree species, leaves grown at elevated CO 2 concentration were significantly reduced in leaf nitrogen concentration and increased in C: N ratio, while neither temperature nor its interaction with CO 2 concentration had any effect. Depending on the tree species, leaf water content declined (red maple) and carbon‐based phenolics increased (sugar maple) on plants grown in an enriched CO 2 atmosphere. The only observed effect of elevated temperature on leaf phytochemistry was a reduction in leaf water content of sugar maple leaves. Gypsy moth larval responses were dependent on tree species. Larvae feeding on elevated CO 2 ‐grown red maple leaves had reduced growth, while temperature had no effect on the growth or consumption of larvae. No significant effects of either temperature or CO 2 concentration were observed for larvae feeding on sugar maple leaves. Our data demonstrate strong effects of CO 2 enrichment on leaf phytochemical constituents important to folivorous insects, while an elevated temperature largely has little effect. We conclude that alterations in leaf chemistry due to an elevated CO 2 atmosphere are more important in this plant–folivorous insect system than either the direct short‐term effects of temperature on insect performance or its indirect effects on leaf chemistry.

Genetic engineering for abiotic stress resistance in crop plants - Jingxian Zhang; Natalya Y. Klueva; Z. Wang; Ray Wu; Tuan-Hua David Ho; Henry T. Nguyen (In Vitro Cellular & Developmental Biology - Plant, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Crustacean resources are vulnerable to serial depletion – the multifaceted decline of crab and shrimp fisheries in the Greater Gulf of Alaska - Janet Armstrong; David Armstrong; Ray Hilborn (Reviews in Fish Biology and Fisheries, 1998)

Leaf age effects of elevated CO 2 ‐grown white oak leaves on spring‐feeding lepidopterans - RaY. S. Williams; David E. Lincoln; Richard J. Norby (Global Change Biology, 1998)
Folivorous insect responses to elevated CO 2 ‐grown tree species may be complicated by phytochemical changes as leaves age. For example, young expanding leaves in tree species may be less affected by enriched CO 2 ‐alterations in leaf phytochemistry than older mature leaves due to shorter exposure times to elevated CO 2 atmospheres. This, in turn, could result in different effects on early vs. late instar larvae of herbivorous insects. To address this, seedlings of white oak ( Quercus alba L.), grown in open‐top chambers under ambient and elevated CO 2 , were fed to two important early spring feeding herbivores; gypsy moth ( Lymantria dispar L.), and forest tent caterpillar ( Malacosoma disstria Hübner). Young, expanding leaves were presented to early instar larvae, and older fully expanded or mature leaves to late instar larvae. Young leaves had significantly lower leaf nitrogen content and significantly higher total nonstructural carbohydrate:nitrogen ratio as plant CO 2 concentration rose, while nonstructural carbohydrates and total carbon‐based phenolics were unaffected by plant CO 2 treatment. These phytochemical changes contributed to a significant reduction in the growth rate of early instar gypsy moth larvae, while growth rates of forest tent caterpillar were unaffected. The differences in insect responses were attributed to an increase in the nitrogen utilization efficiency (NUE) of early instar forest tent caterpillar larvae feeding on elevated CO 2 ‐grown leaves, while early instar gypsy moth larval NUE remained unchanged among the treatments. Later instar larvae of both insect species experienced larger reductions in foliage quality on elevated CO 2 ‐grown leaves than earlier instars, as the carbohydrate:nitrogen ratio of leaves substantially increased. Despite this, neither insect species exhibited changes in growth or consumption rates between CO 2 treatments in the later instar. An increase in NUE was apparently responsible for offsetting reduced foliar nitrogen for the late instar larvae of both species.

Integrated measures of ambient toxicity and fish community diversity in Chesapeake Bay tributaries - S. Ian Hartwell; Celia E. Dawson; Eric Q. Durell; Ray W. Alden; Peter C. Adolphson; David A. Wright; Gina M. Coelho; John A. Magee (Ecotoxicology, 1998)

Relationships of chestnut species and New Zealand chestnut selections using morpho-nut characters - Nnadozie C. Oraguzie; David L. McNeil; David J. Klinac; Ray D. Knowles; J. Richard Sedcole (Euphytica, 1998)

Effects of elevated CO 2 ‐grown loblolly pine needles on the growth, consumption, development, and pupal weight of red‐headed pine sawfly larvae reared within open‐topped chambers - RAY WILLIAMS; DAVID LINCOLN; RICHARD THOMAS (Global Change Biology, 1997)
Seedlings of loblolly pine, Pinus taeda , were grown in open‐topped chambers under four levels of CO 2 : two ambient and two elevated. Larvae of the red‐headed pine sawfly, Neodiprion lecontei , were reared from early instar to pupation, primarily on branches within chambers. Larval growth and mortality were assessed and leaf phytochemistry samples of immature and mature leaves collected weekly. Mature leaves grown under elevated CO 2 had significant reductions in leaf nitrogen and increases in non‐structural carbohydrate contents, resulting in foliage being a poorer food source for larvae, i.e. higher carbohydrate:nitrogen ratio. Nutritional constituents of immature needles were unaffected by seedling CO 2 treatment. Volatile mono‐ and sesquiterpenes were unrelated to plant CO 2 treatments for either leaf age class. Larval consumption of immature needles significantly increased on seedlings grown under CO 2 enrichment, while mature needle consumption was not different between the treatments. The average weight gain per larva significantly declined in late instar larvae consuming elevated CO 2 ‐grown needles. In spite of this reduced growth, neither the days to pupation nor pupal weights were different among the CO 2 treatments. This study suggests that enriched CO 2 ‐induced alterations in pine needle phytochemistry can affect red‐headed pine sawfly performance. However, compensatory measures by larvae, such as choosing to consume more nutritious immature needles, apparently helps offset enriched CO 2 ‐induced reductions in the leaf quality of mature needles.

Susceptibility of potato varieties and advanced breeding lines (Solanum tuberosum L.) toPhytophthora infestans (Mont.) de Bary in greenhouse screenings - David S. Douches; William W. Kirk; Kazimierz Jastrzebski; Christopher Long; Ray Hammerschmidt (American Journal of Potato Research, 1997)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)